Low-smoke halogen-free fireproof cable
By using DOPO derivatives and spinel-type metal oxides as flame retardants in the outer sheath of low-smoke halogen-free cables, combined with low-density polyethylene, EVA resin and other materials, the problem of difficult to take into account both fire resistance and mechanical properties in the prior art is solved, and efficient and environmentally friendly flame retardant effects and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202510294006.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The existing low-smoke halogen-free cables are difficult to maintain good mechanical properties while improving fire resistance, and there are problems with the thermal stability and processability of the flame retardant.
The outer sheath consists of low-density polyethylene, EVA resin, SEBS elastomer, POE-g-GMA, flame retardant, filler and additive. The flame retardant is composed of DOPO derivatives and spinel-type metal oxides. By carefully formulating the formulation of each raw material, the comprehensive performance optimization is achieved.
It realizes the efficient flame retardant effect of low-smoke, halogen-free fire-proof cable, reduces the smoke and heat release during combustion, improves the mechanical properties and service life of the cable, and ensures the environmental protection of the material and the convenience of processing.
Smart Images

Figure CN119775656A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cables, in particular to a low-smoke, halogen-free, fire-proof cable. Background Art
[0002] With the rapid development of economy and society, the application and demand of cables in various fields are increasing. Cable sheaths containing halogen flame retardants will produce a lot of smoke and harmful gases when burning, which will increase the risk of fire rescue. Therefore, halogen-free, low-smoke and flame-retardant wires and cables have become an important research direction.
[0003] The current mainstream low-smoke halogen-free cables are based on polyolefins and are flame-retardant with inorganic or organic flame retardants. Inorganic flame retardants have low flame retardant efficiency, high additions lead to a significant decrease in the mechanical properties of the material, such as tensile strength and flexibility, high processing difficulty, and the inability to form a stable carbon layer to inhibit combustion. Organic flame retardants such as DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) have poor thermal stability and are easy to decompose during processing. Therefore, how to achieve the synergy of multiple flame retardants through compounding, while improving the fire resistance of the cable while still having good mechanical properties has become a problem that needs to be solved urgently. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a low-smoke, halogen-free, fire-resistant cable.
[0005] The technical solutions adopted are as follows: A low-smoke, halogen-free, fire-resistant cable comprising an outer sheath; The outer sheath is made of the following raw materials in parts by weight: 40-60 parts of low-density polyethylene, 20-30 parts of EVA resin, 10-20 parts of SEBS elastomer, 5-10 parts of POE-g-GMA, 5-10 parts of flame retardant, 15-30 parts of filler, 1-5 parts of additives; The flame retardant is composed of an organic component and a spinel metal oxide; The organic component includes a DOPO derivative and a nitrogen-based flame retardant; The structural formula of the DOPO derivative is shown in the following formula (1): ; Wherein, R1, R2, R3, and R4 are each independently hydrogen or a structure shown in formula (2) and R1, R2, R3, and R4 are not hydrogen at the same time. In formula (2), is the connection site with the oxygen atom in formula (1) .
[0006] Furthermore, the structural formula of the DOPO derivative is as follows: .
[0007] Furthermore, the preparation method of the DOPO derivative is as follows: Pentaerythritol reacts with 4-maleimidobenzoic acid to obtain an intermediate, and the intermediate is then added with DOPO to obtain the DOPO derivative.
[0008] Furthermore, the spinel metal oxide is ZnFe2O4.
[0009] Furthermore, the mass ratio of the organic component to the spinel metal oxide is 1:0.1-1.
[0010] Furthermore, the mass ratio of the organic component to the spinel metal oxide is 1:0.25.
[0011] Furthermore, the mass ratio of the DOPO derivative to the nitrogen-based flame retardant is 1-10:1-10.
[0012] Furthermore, the mass ratio of the DOPO derivative to the nitrogen-based flame retardant is 1:1.
[0013] Furthermore, the nitrogen-based flame retardant is at least one of melamine, melamine cyanurate, and melamine polyphosphate, preferably melamine cyanurate.
[0014] Furthermore, the filler is composed of montmorillonite and carbon black in a mass ratio of 1-5:1-5.
[0015] Furthermore, the filler consists of montmorillonite and carbon black in a mass ratio of 1:1.
[0016] Furthermore, the auxiliary agent includes a lubricant and an antioxidant.
[0017] Furthermore, the lubricant is PE wax and / or oxidized PE wax.
[0018] Further, it also includes a cable core consisting of a conductor and a cross-linked polyethylene inner sheath; The outer side of the cable core is sequentially coated with an aluminum-plastic composite wrapping tape, a mica wrapping tape and the outer sheath.
[0019] It has the following beneficial effects: The present invention provides a low-smoke, halogen-free, fireproof cable. The outer sheath can not only protect the conductor and other structural components inside the cable from the influence of the external environment, such as mechanical damage, chemical corrosion, moisture erosion, etc., but also ensure that the cable maintains stability and reliability during long-term operation, and prolongs the service life of the cable. Moreover, the low-smoke, halogen-free, fire-proof cable does not contain halogen, and produces less smoke and heat when encountering a fire, which can effectively prevent the spread of the fire and buy precious time for personnel evacuation and fire rescue. The raw material formula of the outer sheath of the present invention is a carefully formulated system, each raw material performs its own function, and together gives the outer sheath excellent comprehensive performance. Among them, low-density polyethylene is used as a basic raw material to provide basic flexibility and good processing performance for the outer sheath, making the outer sheath easy to shape.
[0020] The presence of vinyl acetate monomer in the molecular structure of EVA resin weakens the crystallization between polyethylene chain segments and enhances the activity of the molecular chain. This feature effectively improves the flexibility of the outer sheath, making it softer and easier to bend while maintaining a certain strength.
[0021] SEBS elastomer is a styrene thermoplastic elastomer. Its microstructure is composed of polystyrene hard segments and polybutadiene soft segments. This special structure makes SEBS show rubber-like high elasticity at room temperature, giving the outer sheath excellent tensile and compression properties. In actual use, the outer sheath can withstand large external force deformation without permanent damage, and quickly returns to its original state after being stressed, effectively improving the product's anti-deformation ability and durability.
[0022] As a compatibilizer, POE-g-GMA contains polar groups and non-polar groups in its molecular structure, which form bridges between different polymers, reduce interfacial tension, enable them to be better dispersed and mixed, improve the compatibility of the entire system, and ensure the uniformity and stability of the outer sheath material. It can also chemically react or physically entangle with other polymers to form a network-like structure. This structure enhances the interaction between polymers and improves the mechanical indicators of the outer sheath, such as tensile strength, tear strength and impact resistance.
[0023] DOPO contains phosphorus in its molecular structure. Under high temperature conditions, phosphorus will undergo a series of chemical reactions. When exposed to a fire source, DOPO decomposes to generate phosphorus-containing free radicals. These free radicals can react with highly active free radicals generated during the combustion of polymers, capture them and convert them into relatively stable substances, thereby interrupting the free radical chain transfer of the combustion reaction and inhibiting the continued combustion. Compared with DOPO, the DOPO derivatives in the flame retardant of the present invention introduce hydroxyl and benzene ring structures. The benzene ring can provide a rigid skeleton to increase thermal stability and will not decompose during processing. The hydroxyl group optimizes the flame retardant mechanism through chemical bonding and carbonization. The two work together to enhance the thermal stability and carbonization efficiency of DOPO, significantly improving its flame retardant properties, so that the DOPO derivatives can achieve efficient, long-lasting and environmentally friendly flame retardant effects in the outer sheath of the cable.
[0024] Nitrogen flame retardants exert flame retardant effects based on the synergistic effects of gas phase flame retardancy and condensed phase flame retardancy. In the gas phase, nitrogen flame retardants decompose under heat to produce non-combustible gases such as ammonia and nitrogen, which dilute the concentration of combustible gases and inhibit the combustion reaction. In the condensed phase, nitrogen flame retardants decompose to form a dense carbonaceous layer, which can isolate oxygen and heat and prevent further spread of combustion. Nitrogen flame retardants and DOPO derivatives can achieve efficient flame retardancy through multiple paths such as gas phase free radical inhibition, condensed phase carbon layer strengthening, and acid source-gas source complementation.
[0025] Spinel metal oxides have a unique spinel structure, which gives them special physical and chemical properties. When working in synergy with DOPO derivatives, spinel metal oxides can promote the phosphorus-containing free radicals produced by the decomposition of DOPO derivatives to more effectively capture combustion free radicals, enhance the ability to inhibit the combustion chain reaction, and further reduce the combustion rate. Spinel metal oxides can participate in the formation of the carbonaceous layer at high temperatures. It can make the carbonaceous layer more dense and stable, enhance its heat insulation and oxygen isolation properties, thereby better blocking the transfer of oxygen and heat, and providing more effective protection for the outer sheath during combustion. In addition, spinel metal oxides themselves can also undergo some physical and chemical changes at high temperatures, absorb part of the heat, and assist in reducing the temperature of the outer sheath. Together with other flame retardants, they build a multi-level, all-round flame retardant system, significantly enhancing the overall flame retardant effect of the outer sheath and improving its safety in fires. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the structure of the low-smoke halogen-free fireproof cable in Example 1, in which the reference numerals represent: 1-Copper conductor, 2-cross-linked polyethylene inner sheath, 3-aluminum-plastic composite tape, 4-mica wrapping tape, 5-outer sheath. DETAILED DESCRIPTION
[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0028] Low-density polyethylene: PE1018, ExxonMobil; EVA resin: 2315, Hanwha, South Korea; SEBS elastomer: G1650MU, Kraton, USA; POE-g-GMA: SH035, Dongguan Shenghao Plastic Raw Materials Co., Ltd.; DOPO derivatives: homemade; Melamine cyanurate: FR-MCA, Dongguan Xingyuan Chemical Co., Ltd.; ZnFe2O4: China Science and Technology Research Institute (Beijing) Technology Co., Ltd.; Montmorillonite: Hebei Hengyue Mineral Products Co., Ltd.; Carbon black N330: Shandong Kasong New Materials Co., Ltd. PE wax: JRF-200, Shanghai Kumho Sunny Plastics Co., Ltd.; Antioxidant 1010: JY-1010, Beijing Jiyi New Materials.
[0029] Embodiment 1: A low-smoke, halogen-free, fire-proof cable, comprising a cable core consisting of a copper conductor 1 and a cross-linked polyethylene inner sheath 2; The outer side of the cable core is sequentially coated with an aluminum-plastic composite tape 3, a mica wrapping tape 4 and an outer sheath 5; By weight, the outer sheath 5 is made of the following raw materials: 50 parts of low-density polyethylene, 25 parts of EVA resin, 15 parts of SEBS elastomer, 8 parts of POE-g-GMA, 10 parts of flame retardant, 10 parts of montmorillonite, 10 parts of carbon black N330, 1 part of PE wax, 1 part of antioxidant 1010; The flame retardant is composed of 4 parts of DOPO derivative, 4 parts of melamine cyanurate and 42 parts of ZnFe2O; The structural formula of DOPO derivatives is shown below: .
[0030] The preparation method of DOPO derivatives is as follows: ; S1: In a dry reaction bottle, dissolve 4-maleimidobenzoic acid (e.g., 20 mmol) in anhydrous DMF (200 ml), cool to 0-5°C in an ice bath, slowly add DCC (22 mmol), then add DMAP (0.5 mmol), stir for 30 min, add pentaerythritol (10 mmol) to the solution, remove the ice bath, raise the temperature to 40°C, stir and react for 12 h, return to room temperature after the reaction, filter, and concentrate the filtrate on a rotary evaporator. Dissolve the residue in ethyl acetate (300 mL), wash with 5% dilute hydrochloric acid, saturated sodium bicarbonate solution, and deionized water in turn, and finally dry over anhydrous sodium sulfate and concentrate under reduced pressure to obtain the intermediate.
[0031] ; The intermediate (5 mmol) and DOPO (10 mmol) were added to 200 ml methanol, heated to 55 °C with stirring for 10 h, and the methanol was distilled off under reduced pressure after the reaction. 20 ml of dichloromethane and 100 ml of ethyl acetate were added for recrystallization to obtain the DOPO derivative with a yield of 50.3%. ESI-MS (m / z) (M + ): Theoretical value 966.83, measured value 966.46.
[0032] The preparation method of the outer sheath granules is as follows: The raw materials are placed in a high-speed mixer, mixed at 80°C for 10 minutes, and then transferred to a twin-screw extruder. The aspect ratio of the twin-screw extruder is 40:1, the screw speed is 200-300 rpm, the temperature of zone 1 is 120-140°C, the temperature of zone 2 is 150-160°C, the temperature of zone 3 is 160-170°C, the temperature of zone 4 is 170-180°C, and the temperature of the die head is 175-185°C. The extruded material strips are cooled in a water cooling tank and then pelletized to obtain outer sheath pellets.
[0033] Embodiment 2: A low-smoke, halogen-free, fire-proof cable, comprising a cable core consisting of a conductor 1 and an inner sheath 2; The outer side of the cable core is covered with an aluminum-plastic composite tape 3, a mica tape 4 and an outer sheath 5 in sequence; By weight, the outer sheath 5 is made of the following raw materials: 60 parts of low-density polyethylene, 30 parts of EVA resin, 20 parts of SEBS elastomer, 10 parts of POE-g-GMA, 10 parts of flame retardant, 10 parts of montmorillonite, 10 parts of carbon black N330, 1 part of PE wax, 1 part of antioxidant 1010; The flame retardant is composed of 4 parts of DOPO derivative, 4 parts of melamine cyanurate and 42 parts of ZnFe2O; The structural formula and preparation method of the DOPO derivative are the same as those in Example 1.
[0034] The preparation method of the outer sheath granules is as follows: The raw materials are placed in a high-speed mixer, mixed at 80°C for 10 minutes, and then transferred to a twin-screw extruder. The aspect ratio of the twin-screw extruder is 40:1, the screw speed is 200-300 rpm, the temperature of zone 1 is 120-140°C, the temperature of zone 2 is 150-160°C, the temperature of zone 3 is 160-170°C, the temperature of zone 4 is 170-180°C, and the temperature of the die head is 175-185°C. The extruded material strips are cooled in a water cooling tank and then pelletized to obtain outer sheath pellets.
[0035] Embodiment 3: A low-smoke, halogen-free, fire-proof cable, comprising a cable core consisting of a conductor 1 and an inner sheath 2; The outer side of the cable core is covered with an aluminum-plastic composite tape 3, a mica tape 4 and an outer sheath 5 in sequence; By weight, the outer sheath 5 is made of the following raw materials: 40 parts of low-density polyethylene, 30 parts of EVA resin, 10 parts of SEBS elastomer, 5 parts of POE-g-GMA, 10 parts of flame retardant, 10 parts of montmorillonite, 10 parts of carbon black N330, 1 part of PE wax, 1 part of antioxidant 1010; The flame retardant is composed of 4 parts of DOPO derivative, 4 parts of melamine cyanurate and 42 parts of ZnFe2O; The structural formula and preparation method of the DOPO derivative are the same as those in Example 1.
[0036] The preparation method of the outer sheath granules is as follows: The raw materials are placed in a high-speed mixer, mixed at 80°C for 10 minutes, and then transferred to a twin-screw extruder. The aspect ratio of the twin-screw extruder is 40:1, the screw speed is 200-300 rpm, the temperature of zone 1 is 120-140°C, the temperature of zone 2 is 150-160°C, the temperature of zone 3 is 160-170°C, the temperature of zone 4 is 170-180°C, and the temperature of the die head is 175-185°C. The extruded material strips are cooled in a water cooling tank and then pelletized to obtain outer sheath pellets.
[0037] Comparative Example 1: It is basically the same as Example 1, except that SEBS elastomer is not added to the raw material of the outer sheath 5.
[0038] Comparative Example 2: The method is basically the same as Example 1, except that POE-g-GMA is not added to the raw material of the outer sheath 5 .
[0039] Comparative Example 3: The method is substantially the same as Example 1, except that the flame retardant does not contain DOPO derivatives.
[0040] Comparative Example 4: The method is substantially the same as Example 1, except that DOPO is used to replace the DOPO derivative in the flame retardant.
[0041] Comparative Example 5: The method is substantially the same as Example 1, except that the flame retardant does not contain melamine cyanurate.
[0042] Comparative Example 6: It is basically the same as Example 1, except that the flame retardant does not contain ZnFe2O4.
[0043] Comparative Example 7: The method is basically the same as Example 1, except that ZnFe2O4 in the flame retardant is replaced by ZnO.
[0044] Performance Testing The outer sheath granules in Examples 1-3 of the present invention and Comparative Examples 1-7 were made into test pieces for performance testing.
[0045] The tensile strength is tested in accordance with the provisions of GB / T 1040.3-2006 “Determination of tensile properties of plastics Part 3 Test conditions for films and sheets”, the specimen is type 5, and the tensile rate is 100 mm / min.
[0046] Limiting oxygen index (LOI) test: Tested on an oxygen index tester according to ASTM D2863-77 standard, the size of the sample is 100mm×6.5mm×3mm.
[0047] According to the GB / T 2408-2008 test standard, the UL-94 vertical burning level was measured using a vertical burning test instrument (ZY6017), and the size of the sample was 130mm×13mm×3mm.
[0048] The ISO5660-1 standard test sample is used to test the changes in heat release and smoke release over time during combustion. The radiation power is 50kW, the size of the sample is 100mm×100mm×3mm, and the total heat release (THR) and total smoke release (TSR) are measured.
[0049] The test results are shown in Table 1 below: Table 1:
[0050] It can be seen from Table 1 above that the outer sheath granules prepared by the present invention have excellent mechanical properties and extremely good fire retardant properties. Not only does it have a high flame retardant grade, but it also produces little heat and smoke after combustion. It is an excellent material for preparing low-smoke halogen-free fireproof cables.
[0051] By comparing Example 1 with Comparative Examples 1-2, it can be seen that the addition of SEBS elastomer and POE-g-GMA plays a positive role in improving the mechanical properties of the outer sheath; By comparing Example 1 with Comparative Examples 3 and 5, it can be seen that the addition of DOPO derivatives, melamine cyanurate and ZnFe2O4 plays a positive role in improving the fire retardant properties of the outer sheath; By comparing Example 1 with Comparative Example 4, it can be seen that, compared with DOPO, the addition of DOPO derivatives has a greater improvement in the fire retardant properties of the outer sheath.
[0052] By comparing Example 1 with Comparative Example 6, it can be seen that, compared with ZnO, the addition of ZnFe2O4 has a greater improvement in the fire retardant properties of the outer sheath.
[0053] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low smoke halogen-free fireproof cable, characterized in that: Including outer sheath; The outer sheath is made of the following raw materials in parts by weight: 40-60 parts of low-density polyethylene, 20-30 parts of EVA resin, 10-20 parts of SEBS elastomer, 5-10 parts of POE-g-GMA, 5-10 parts of flame retardant, 15-30 parts of filler, 1-5 parts of additives; The flame retardant is composed of an organic component and a spinel metal oxide; The organic component includes a DOPO derivative and a nitrogen-based flame retardant; The structural formula of the DOPO derivative is shown in the following formula (1): ; Wherein, R1, R2, R3, and R4 are each independently hydrogen or a structure shown in formula (2) and R1, R2, R3, and R4 are not hydrogen at the same time. In formula (2), is the site of attachment to the oxygen atom in formula (1); 。 2. The low smoke zero halogen fireproof cable according to claim 1, characterized in that: The structural formula of the DOPO derivative is shown below: 。 3. The low smoke zero halogen fireproof cable according to claim 2, characterized in that: The preparation method of the DOPO derivative is as follows: Pentaerythritol reacts with 4-maleimidobenzoic acid to obtain an intermediate, and the intermediate is then added with DOPO to obtain the DOPO derivative.
4. The low smoke zero halogen fireproof cable according to claim 1, characterized in that: The spinel metal oxide is ZnFe2O4.
5. The low smoke zero halogen fireproof cable according to claim 1, characterized in that: The mass ratio of the organic component to the spinel metal oxide is 1:0.1-1.
6. The low smoke zero halogen fireproof cable according to claim 1, characterized in that: The mass ratio of the DOPO derivative to the nitrogen-based flame retardant is 1-10:1-10.
7. The low smoke zero halogen fireproof cable according to claim 1, characterized in that: The nitrogen-based flame retardant is at least one of melamine, melamine cyanurate and melamine polyphosphate.
8. The low smoke zero halogen fireproof cable according to claim 1, characterized in that: The filler consists of montmorillonite and carbon black in a mass ratio of 1-5:1-5.
9. The low smoke zero halogen fireproof cable according to claim 1, characterized in that: The auxiliary agents include lubricants and antioxidants.
10. The low smoke zero halogen fire resistant cable according to any one of claims 1 to 9, characterized in that: Also included is a cable core consisting of a conductor and a cross-linked polyethylene inner sheath; The outer side of the cable core is sequentially coated with an aluminum-plastic composite wrapping tape, a mica wrapping tape and the outer sheath.
Citation Information
Patent Citations
Flame-retardant resin composition and prepreg and laminate prepared using same
CN109535715A
Polyamide wax as well as preparation method and application thereof
CN114920927A
Low-dielectric flame-retardant layer-adding adhesive film for FCBGA packaging carrier plate and preparation method of low-dielectric flame-retardant layer-adding adhesive film
CN116042157A
Low-smoke halogen-free flame-retardant cable
CN116386943A
Halogen-free flame-retardant polyurethane cable sheath material and preparation method thereof
CN118290926A
Cited By
Aluminum alloy cable
CN120767050A
Aluminum alloy cable
CN120767050B
Low-smoke non-toxic fireproof flame-retardant cable
CN121331550A